Influência da cobertura morta na evapotranspiração, coeficiente de cultivo e eficiência de uso de água do milho cultivado em cerrado. - Murga-Orrillo, H. (2016)
Irrigation consumes large amounts of water, and minimizing consumption and maximizing the production are important to a proper crop management . In order to obtain information for irrigation management, the aim of the present study was to determine evapotranspiration (ETc), crop coefficient (Kc) and water use efficiency (WUE) of maize grown in soil with and without cover, duringthe various stages of development, using drainage lysimeters. The experiment was conducted in Cauamé campus of the Federal University of Roraima, from 19/04/2014 to 08/07/2014, in Boa Vista, RR. The reference evapotranspiration (ETo) was estimated by the Penman-Monteith method. The results of the corn ETc during the crop cycle in soil with and without coverage were 421.5 and 351.0 mm, respectively. The daily average of ETc were 4.1 mm day-1 for bare soil and 3.4 mm day-1 for soil with cover. The ground cover led to different values of Kc's for corn in the same stages as compared to Kc's from the bare ground. For bare soil, the Kc's observed for the phenological stages I, II, III, and IV were 0.40; 0.84; 1.59 and 0.81, respectively. As for covered soil, the Kc's in the same stadiums mentioned were 0.28; 0.64; 1.49 and 0.48, respectively. The WUE to soil with cover was 1.77 kg m-3 and ground without cover was 1.65 kg m-3. These results show that soil mulching influenceS maize water consumption throughout its cycle.